Nel regno del fango : speleoarcheologia della Grotta di Polla (Salerno, Italia) : risultati delle prime campagne di scavo - Minelli, Antonella; Guglielmi, Sandra (Access archaeology., 2020)
Presents the preliminary results of the archaeological excavations carried out in the Grotta di Polla, in the province of Salerno, Italy. The challenges of speleoarchaeology are discussed, and the methodologies adopted for the preservation and conservation of archaeological materials and the results obtained are illustrated.